O-05 Differences in alpha and beta oscillations in subthalamic nucleus of Parkinsonian patients. Issue 7 (July 2019) - Belova, Elena; Semenova, Ulia; Gamaleya, Anna; Tomskiy, Alexey; Medvednik, Rita; Sedov, Alexey
Abstract : Rhythmic activity in basal ganglia is studied intensively as it may imply in pathophysiological sympthoms of Parkinson's disease (PD). Several researchers associate beta oscillations with the severity of disease manifestations. However, some studies review alpha (8–12 Hz) and low beta (13–30 Hz) activity together, without drawing distinctions between specific features of these oscillations. According to Horn et al. (2017), alpha activity may be linked to associative regions of STN, whereas beta activity were found in motor areas. Our aim was to compare alpha and beta oscillations in STN under PD concerning their features, distribution and clinical implications in PD. LFP records from 31 parkinsonian patients undergoing DBS surgeries were included in the study. Spectra with significant alpha (8–12 Hz) or beta (12–30, 30–40 Hz) were investigated separately. Location of rhythmic activity were determined using Lead DBS Software. We found that significant beta oscillations were located more dorso-laterally compared to alpha oscillations in ventro-medial STN regions. We have also found moderate correlation between low beta oscillation score and UPDRS3 score in on- and off-state. Alpha activity were more stable in time and were almost insensitive to motor tests performed during the surgery. These results indicate that alpha and beta oscillations must be reviewed and studied independently, and alpha oscillations may probably serve as indicator for proximity to associative regions in STN during DBS surgeries. This work was supported within frameworks of the state task forICP RAS 0082-2014-0001 (state registration #AAAA-A17-117040610310-6) andRFBR grant#18-015-00140 .